Thermal performance of a diffusion absorption refrigeration system driven by waste heat from diesel engine exhaust gases. (5th March 2017) - Aly, Wael I.A.; Abdo, Mohammed; Bedair, Gamal; Hassaneen, A.E.
Highlights: Performance of DAR using diesel engine waste heat was experimentally evaluated. Maximum COP of 0.10 obtained for the controlled exhaust flow case at 30 N m torque. Maximum of almost 9% waste heat recovery is achieved for the current system. Refrigerator reached a temperature 10–14.5 °C about 3.5 h depending on engine load. Abstract: The thermal performance of a diffusion absorption refrigerator (DAR) driven by the waste heat of a diesel engine exhaust gas as an energy source was investigated experimentally. The engine was tested on a bench test dynamometer with the DAR adapted to the exhaust pipe via a heat exchanger. The engine was tested for different torques (15, 30 and 45 N m). The exhaust gas flow to the heat exchanger mounted on the DAR was controlled manually using two control valves. The experimental results indicated that by controlling exhaust gas flow, the DAR system was capable to function in a broad range of engine loads. The refrigerator cabin reached a steady state temperature between 10 and 14.5 °C about 3.5 h after system startup, depending on engine load. The maximum coefficient of performance was 0.10 obtained for the controlled exhaust mass flow rate case at torque 30 N m after 3 h from system startup. Also, a maximum of almost 10% waste heat recovery is achieved in the current system.